2005
DOI: 10.1097/01.gme.0000170603.63022.62
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a combination of isoflavones and Actaea racemosa Linnaeus on climacteric symptoms in healthy symptomatic perimenopausal women: a 12-week randomized, placebo-controlled, double-blind study

Abstract: The supplement containing soy isoflavones and A racemosa L. had no statistically significant effect on climacteric symptoms in perimenopausal women experiencing at least five vasomotor symptoms per day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 28 publications
1
18
1
5
Order By: Relevance
“…The topic has been adequately reviewed and overall evidence shows that phytoestrogen extracts of soy and red clover have little or no effect; at best only 10% reduction of symptoms beyond that of the placebo effect (Kurzer 2003, Geller & Studee 2005. Some studies have shown that black cohosh reduced symptoms, primarily hot flushes and mood disorders (Geller & Studee 2005, Viereck et al 2005, but recent studies have shown no significant effects of this extract on hot flushes (Newton et al 2005, Verhoeven et al 2005.…”
Section: Efficacy Of Phytoestrogens As Alternatives To Hrtmentioning
confidence: 99%
“…The topic has been adequately reviewed and overall evidence shows that phytoestrogen extracts of soy and red clover have little or no effect; at best only 10% reduction of symptoms beyond that of the placebo effect (Kurzer 2003, Geller & Studee 2005. Some studies have shown that black cohosh reduced symptoms, primarily hot flushes and mood disorders (Geller & Studee 2005, Viereck et al 2005, but recent studies have shown no significant effects of this extract on hot flushes (Newton et al 2005, Verhoeven et al 2005.…”
Section: Efficacy Of Phytoestrogens As Alternatives To Hrtmentioning
confidence: 99%
“…Os extratos dessa planta f oram usados historicamente como antiinflamatórios, antipiréticos e analgésicos dentre outras indicações, como no tratamento das cólicas menstruais e nos sintomas da menopausa (Bolle et al, 2007). Recentemente passou a ser utilizado em todo mundo, mas principalmente nos Estados Unidos e na Europa, por mulheres para aliviar os sintomas do climatério (Vermes et al, 2005).…”
Section: Atividades Farmacológicas Evidenciadasunclassified
“…Entre as principais ações estão a diminuição intensa dos fogachos (Mahady et al, 2002;Vermes et al, 2005); a diminuição da ansiedade, depressão, cefaléia, distúrbios do sono e vertigens (Borreli & Ernst, 2002;Vermes et al, 2005) e a melhora acentuada da atrofia vaginal (Wuttke et al, 2003b).…”
Section: Atividades Farmacológicas Evidenciadasunclassified
See 1 more Smart Citation
“…Até o momento, não existem dados que suportem seu Rev Bras Ginecol Obstet. 2006; 28(3): 195-204 uso na prática clínica 56 . Com a finalidade de avaliar o impacto dos fitoestrogênios na QV e nos sintomas climatéricos de mulheres com câncer de mama, realizou-se estudo aleatorizado, duplo-cego, controlado com placebo.…”
Section: Síndrome Climatéricaunclassified